HUBUNGAN DIET RENDAH KARBOHIDRAT DENGAN KADAR GLUKOSA DARAH: SYSTEMATIC LITERATURE REVIEW: THE RELATIONSHIP BETWEEN A LOW-CARBOHYDRATE DIET AND BLOOD GLUCOSE LEVELS: A SYSTEMATIC LITERATURE REVIEW - Bella Ayuningtyas; Farapti (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2026)
Background: The increasing prevalence of uncontrolled blood glucose levels has become a significant global health problem. One of the commonly used approaches for glycemic control is a low-carbohydrate diet. Objective: To determine the relationship between a low-carbohydrate diet and blood glucose levels based on a literature review. Methods: This study was a literature review conducted using PubMed and Cochrane databases. Article searches were performed using the keywords (“low carbohydrate diet”) AND (“blood glucose” OR “glycemic control”). Inclusion criteria included international articles, human subjects, availability of free full-text, and publication within the last 10 years. The selection process was carried out using the PRISMA diagram, resulting in 7 articles that met the criteria for analysis. Results: Most studies showed that a low-carbohydrate diet significantly reduced fasting blood glucose, 2-hour postprandial blood glucose, and HbA1c levels (p < 0.05). Several studies indicated that low-carbohydrate diet was more effective compared to other dietary approaches, such as the Mediterranean diet and low-fat diet. However, some studies reported no significant differences between intervention groups, despite reductions observed within each group. Conclusion: A low-carbohydrate diet is an effective approach for controlling blood glucose levels, with very low-carbohydrate diets (VLCD) or ketogenic diets being the most effective types. However, its effectiveness may vary depending on individual conditions and intervention characteristics.